The Protection of Fundamental Human Rights in the context of the Global Fight against Terrorism - Diallo, Bubacar Sidi (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2023)
Terrorism poses a serious threat in the world today. Although it does not affect all countries to the same extent, the international community must cooperate to develop measures to effectively eradicate this common enemy. Despite the increasing number of international treaties aimed at regulating the fight against terrorism and terrorism-related acts, terrorism continues to thrive around the world, and as a result, has a significant impact on human rights. This article examines some anti-terrorist measures at the universal level and aims to determine to what extent they may infringe upon fundamental human rights. This article also highlights the importance of fundamental human rights and the risk of them being violated in the global fight against terrorism. There is no doubt that terrorism has devastating consequences on the exercise of human rights, including the right to live, the right to liberty and the physical integrity of victims as well as the individuals suspected of committing terrorist acts. The research was conducted using primarily the dogmatic method, followed by an analysis of international legal instruments. The analysis proved that the measures taken internationally in response to terrorism-related attacks may not only violate fundamental human rights but also undermine the rule of law and hinder the protection of some basic human rights. It is important, therefore, that States find a right balance between fulfilling their two obli gations: ensuring security of their citizens and fighting terrorism.